Design of the Temperature Control System with the MicroLogix - Sui Tao; Sun Fanchao; Li Lijun; Liu Ruijuan; Qi Ranran (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The design and verification of accurate temperature control system of the oven with the small or middle scale programmable logic controller (PLC) base on the dahlin algorithm is introduced. The design can achieve accurate control to the pure lag system and regulate the other logic control form the same controller. The system is cost-effective on the specific modular or instrument for the complex computing in some automatic device. Meanwhile, the design is computed and simulated by the matlab softwear for verifying the implementation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3101